DEVELOPMENT OF LEARNING SET BASED ON SCIENTIFIC APPROACH IN THE TOPIC OF CIRCLE TO IMPROVE STUDENTS' MATHEMATICS LEARNING ACHIEVEMENT FOR JUNIOR HIGH SCHOOL GRADE VIII - Kumala Kusuma Putri; Marsigit . (Universitas Negeri Yogyakarta, 2017)
This study aims to produce learning set using scientific approach which comprises lesson planand student worksheet in the topic of circle to improve students' mathematics learning achievement forjunior high school grade VIII which are valid, practical, and effective. Learning set using scientificapproach consists of observing, asking, collecting information, associating, and communicating. Typeof this study is research and development with ADDIE model, which includes Analysis, Design,Development, Implementation, and Evaluation. The instruments which are used in the research namelythe evaluation sheets of learning set to measure validity, questionnaire of response from teacher,questionnaire of responses from students, and observation sheet of learning implementation to measurethe practicality, and mathematics learning achievement test to measure the effectiveness of thelearning set. This research produces learning set in the form of four lesson plan and one studentworksheet. Learning set complies the validity criteria for lesson plan with the average score of 1.00from maximum score of 1.00 for guttman scale and the average score of 4.15 from maximum score of5.00 for likert scale, while for student worksheet with the average of 4.21 from maximum score of5.00. Learning set complies the practicality criteria with the average score of 4.44 for the questionnaireof respone from teacher, 4.15 for the questionnaire of responses from students, from maximum scoreof 5.00, and the average percentage of 93.33% from maximum percentage of 100% for observationsheet of learning implementation. Based on the results analysis of the mathematics learningachievement test, learning set complies the effectiveness criteria, is indicated by the percentage ofstudents completeness in minimum completeness criteria of 87.10%.Keywords: scientific approach, learning set, mathematics learning achievement